Endotoxaemia in haemodialysis: a novel factor in erythropoetin resistance? - Harrison, Laura E.A.; Burton, James O.; Szeto, Cheuk-Chun; Li, Philip K.T.; McIntyre, Christopher W. (Public Library of Science, 2012)
Background/Objectives